2014
DOI: 10.1371/journal.pone.0084072
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Features of Murine Craniofacial and Trunk Neural Crest Cells as Stem Cell-Like Cells

Abstract: The outstanding differentiation capacities and easier access from adult tissues, cells derived from neural crest cells (NCCs) have fascinated scientists in developmental biology and regenerative medicine. Differentiation potentials of NCCs are known to depend on their originating regions. Here, we report differential molecular features between craniofacial (cNCCs) and trunk (tNCCs) NCCs by analyzing transcription profiles and sphere forming assays of NCCs from P0-Cre/floxed-EGFP mouse embryos. We identified up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs)/stromal cells share developmental similarities and differentiation potential with NCCs, consistent with the views that MSCs partially originate from NCCs (Takashima et al 2007;Nagoshi et al 2008;Fukuta et al 2014). For instance, the craniofacial mesenchyme and a subpopulation of bone marrow MSCs developmentally originate from NCCs (Chai et al 2000;Hagiwara et al 2014;Isern et al 2014;Wiszniak et al 2015). Moreover, the mesoderm is a major source of the MSCs that give rise to skeletal and connective tissues (Olsen et al 2000).…”
Section: Discussionsupporting
confidence: 53%
“…Mesenchymal stem cells (MSCs)/stromal cells share developmental similarities and differentiation potential with NCCs, consistent with the views that MSCs partially originate from NCCs (Takashima et al 2007;Nagoshi et al 2008;Fukuta et al 2014). For instance, the craniofacial mesenchyme and a subpopulation of bone marrow MSCs developmentally originate from NCCs (Chai et al 2000;Hagiwara et al 2014;Isern et al 2014;Wiszniak et al 2015). Moreover, the mesoderm is a major source of the MSCs that give rise to skeletal and connective tissues (Olsen et al 2000).…”
Section: Discussionsupporting
confidence: 53%
“…Expression in the long term cultured ectoderm-and XEN-like cells was compared to these tissue expression data sets from the literature: neural progenitor cells 64 , neural crest cells 65 , yolk sac 66 and a XEN cell line 67 .…”
Section: Articlementioning
confidence: 99%
“…The data presented above suggest that the products of pluripotent stem cell‐related genes regulate FoxD3. Furthermore, mouse neural crest‐derived cells have been known to express pluripotent stem cell‐related genes . Therefore, we analyzed the expression of FoxD3 and pluripotent stem cell‐related genes in mouse embryonic DRGs, a typical tissue containing NCSCs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CHD7 and the products of the pluripotent stem cell‐related genes, which contain octamer‐binding transcription factor 3/4 ( Oct3/4 ), Sox2 , and Nanog , colocalize at CHD7 binding sites of target gene enhancers marked with H3K4me1 in ES cells . Furthermore, it has been shown that mouse neural crest cells and mouse neural crest‐derived cells express Oct3/4, Sox2, and Nanog . Thus, these pluripotent stem cell‐related genes may participate in the formation of mouse NCSCs.…”
Section: Introductionmentioning
confidence: 99%